Digital totalitarianism algorithms and society - Filimowicz, Michael (Routledge, 2022)
Digital Totalitarianism: Algorithms and Society focuses on important challenges to democratic values posed by our computational regimes: policing the freedom of inquiry, risks to the personal autonomy of thought, NeoLiberal management of human creativity and the collapse of critical thinking with the social media fueled rise of conspiranoia.